2000
DOI: 10.1016/s0035-9203(00)90123-8
|View full text |Cite
|
Sign up to set email alerts
|

Genital manifestations and reproductive health in female residents of a Wuchereria bancrofti-endemic area in Tanzania

Abstract: To assess the significance of lymphatic filariasis for the development of chronic genital manifestations and for reproductive health in women, we conducted a cross-sectional study of 2 villages in north-eastern Tanzania including interview and gynaecological examination of adult women, focusing primarily on reproductive history and genital health. In a population of 2165 residents, prevalence of Wuchereria bancrofti microfilaraemia was 28%, and geometric mean intensity of microfilariae (mf) was 722 mf/mL. Leg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…Similar to studies in Haiti, India, Thailand, and Africa, the narratives we examined demonstrated the detrimental effect of lymphedema of the leg on psychological and emotional well-being (Bernhard et al, 2000;Coreil et al, 1998;Gyapong, Gyapong, Adjei, Vlassoff, & Weiss, 1996;Rauyajin, Kamthornwachara, & Yablo, 1995). While some variation was expressed, women in this study described similar underlying negative psychological states, emotional reactions, and cognitive responses in the interviews.…”
Section: Psychological Distresssupporting
confidence: 69%
“…Similar to studies in Haiti, India, Thailand, and Africa, the narratives we examined demonstrated the detrimental effect of lymphedema of the leg on psychological and emotional well-being (Bernhard et al, 2000;Coreil et al, 1998;Gyapong, Gyapong, Adjei, Vlassoff, & Weiss, 1996;Rauyajin, Kamthornwachara, & Yablo, 1995). While some variation was expressed, women in this study described similar underlying negative psychological states, emotional reactions, and cognitive responses in the interviews.…”
Section: Psychological Distresssupporting
confidence: 69%
“…Others maintain that filariasis may cause implantation failure of the embryo at the level of the endometrium [7]. Even though pregnancy did not occur through IVF in our reported case, previous cases of W. Bancrofti infections successfully resulted in a complication-free pregnancy following appropriate treatment [12]. One study enrolling 2,165 patients, of which 28% were infected with W. Bancrofti, showed no impact on fertility or pregnancy related complications in infected women [12].…”
Section: Discussionmentioning
confidence: 61%
“…Even though pregnancy did not occur through IVF in our reported case, previous cases of W. Bancrofti infections successfully resulted in a complication-free pregnancy following appropriate treatment [12]. One study enrolling 2,165 patients, of which 28% were infected with W. Bancrofti, showed no impact on fertility or pregnancy related complications in infected women [12]. Therefore, one would not expect a history of W. Bancrofti infection, following treatment, to negatively impact fertility.…”
Section: Discussionmentioning
confidence: 71%
“…The patient described here had idiopathic endometrial inflammation; an additional endometrial biopsy performed after antifilarial treatment was nondiagnostic. The possible association between filarial infection and infertility is an intriguing observation that may deserve further investigation [11]. …”
Section: Diagnosis: Loiasismentioning
confidence: 99%